2007
DOI: 10.1007/s10562-007-9330-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production by Photo-Induced Reforming of Biomass Components and Derivatives at Ambient Conditions

Abstract: Hydrogen can be produced at ambient conditions via an efficient, technologically simple, ecologically benign, and potentially very low-cost process, with the use of a Pt/TiO 2 photocatalyst and three abundant and renewable sources: biomass, solar light, and water. The method combines photocatalytic splitting of water and lightinduced oxidation of biomass compounds into a single process, able to produce hydrogen at room temperature and atmospheric pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
232
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(249 citation statements)
references
References 33 publications
9
232
0
6
Order By: Relevance
“…Under equal testing conditions, photoreforming of organics leads to hydrogen generation rates more than two orders of magnitude higher than photocatalytic water splitting [124]. In this respect, some of the most relevant results collected in the literature review are reported in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Under equal testing conditions, photoreforming of organics leads to hydrogen generation rates more than two orders of magnitude higher than photocatalytic water splitting [124]. In this respect, some of the most relevant results collected in the literature review are reported in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…The feasibility of PR of different biomass-derived compounds has been proved [38] with alcohols, organic acids, and different carbohydrates, such as ribose, arabinose, glucose, galactose, fructose, and mannose. In all cases, the amounts ISRN Chemical Engineering 3 of excess H 2 with respect to simple WS and CO 2 produced are in accordance with the stoichiometry of the following reaction:…”
Section: Materials and Mechanismsmentioning
confidence: 99%
“…Therefore, means for the energetic valorization of this polyalcohol are more than welcome, in light of its increasing availability. 0.5 wt% Pt/TiO 2 was tested for glycerol PR in aqueous solution, increasing the H 2 production rate by one order of magnitude with respect to pure water [38]. Other examples of glycerol PR over Pd/TiO 2 and Au/TiO 2 were proposed in [13], though the catalysts were sensitive to UV light only.…”
Section: Photoreforming Of Alcoholsmentioning
confidence: 99%
“…4B). Incipient methanol can act as a sacrificial agent and in part can be completely oxidized to carbon dioxide and H 2 [23,24]. The data at 5 hours were measured but were under the limit of determinableness which was determined as 12 μg CH 3 OH per L (i.e.…”
Section: Effect Of Calcination Temperaturementioning
confidence: 99%